Associations of black carbon with lung function and airway inflammation in schoolchildren. (October 2019) - Paunescu, Alexandra-Cristina; Casas, Maribel; Ferrero, Amparo; Pañella, Pau; Bougas, Nicolas; Beydon, Nicole; Just, Jocelyne; Lezmi, Guillaume; Sunyer, Jordi; Ballester, Ferran; Momas, Isabelle
Abstract: Background: Few studies have investigated the 24-hour respiratory health effects of personal black carbon (BC) and ultrafine particles (UFP) exposure in schoolchildren. The objective of this study was to investigate these associations with the lung function in children 10-years old with and without persistent respiratory symptoms. Methods: We conducted a cross-sectional study in 305 children (147 and 158 with and without persistent respiratory symptoms, respectively) from three European birth-cohorts: PARIS (France) and INMA Sabadell and Valencia (Spain). Personal 24-hour measurements of exposure concentrations to BC and UFP were performed by portable devices, before lung function testing. Forced expiratory volume in 1 s (FEV1 ), forced vital capacity (FVC) and the fraction of exhaled nitric oxide (FeNO) were determined. Results: There was no association of UFP with lung function parameters or FeNO whereas the increase in 24-hour BC exposure concentrations was related to a statistically significant decrease in lung function parameters only among children with persistent respiratory symptoms [−96.8 mL (95% Confidence Interval CI: −184.4 to −9.1 mL) in FVC, and −107.2 mL (95% CI: −177.5 to −36.9 mL) in FEV1 for an inter-quartile range of 1160 ng/m 3 exposure increase]. A significant positive association between BC and FeNO was observed only in children with persistent respiratory symptoms with current wheezing and/or medication to improve breathing [FeNO increases with +6.9 ppb (95% CI: 0.7 to 13.1 ppb) with an inter-quartile range BC exposure increase]. Conclusion: Children suffering from persistent respiratory symptoms appear to be more vulnerable to BC exposure. Highlights: Personal 24-hour black carbon exposure was measured in schoolchildren. Higher black carbon exposure was associated to decreased lung function parameters. Black carbon exposure was linked to increased FeNO in current symptomatic children.